Inclusionary culture, policies and practices in the education of children with special needs in residential institutions - Jocson, Ellisiah U. (College of Education, University of the Philippines Diliman, 2021)
Inclusion is a global trend in many sectors of society, particularly in education. Delivering the appropriate educational service to people with disabilities has been a long standing battle for the later part of the 20th century. Currently, inclusion is the leading approach in reaching equity and equality in the education of people with disabilities. However, inclusive education is fairly new to the Philippine setting. There is yet to be a conclusive way of implementing inclusion in the Philippine education sector, especially for children with disabilities cared for by residential institutions. This qualitative study seeks to explore if there are traces of inclusive education in residential institutions. Using the indicators of inclusive culture, policies and practices by Booth and Ainscow's (2002) Index for Inclusion, the researcher conducted interviews and observations in a public and private institution. After analysing the data gathered, a comparison of the institutions was made. The study showed that there indeed traces of inclusion in both institutions, with practices that does not inhibit participation, policies that foster participation, and a culture that does not possess exclusivity. However, the data also showed areas that needs improvements. It can be concluded that inclusion has permeated both private and public institutions, but is yet to attain a degree desirable enough to be called truly inclusive.